Associação entre Health Eating Index e obesidade metabolicamente saudável em adolescentes de uma capital do nordeste - Ferreira, Adriana Leão de Miranda (2021)
Introduction:. Adolescence is a phase of transition and relevant changes, becoming a period of nutritional vulnerability to chronic diseases, including obesity. Obesity phenotypes can be divided into Metabolically Health obesity (MHO) and Metabolically Unhealth Obesity (MUO). Among the etiological factors of MHO, that may be associated with this favorable metabolic profile is eating healthy. The a priori method, that use indices, has been used to asses the diet quality of adolescents and to verify differences between metabolic profiles. Among the indexes based on scores, we highlight the Health Eating Index (HEI). Objectives: To acess the association between diet quality throught the HEI with MHO and MUO in adolescents and associated factors. Metodology: Cross-Sectional study, by non-probabilisticsampling, with overweight and obese adolescents, attended at the Pediatric Endocrinology Outpatient Clinical of University Hospital Onofre Lopes during Octoberof 2016 and February of 2020. Biodemographic data (physical activity and sleep hours), food consumption (24-hour recall), anthropometric data (weight, height, BMI- Body Mass Index, waist-to-height-ratio, waist and blood pressure) and biochemical data (lipid profile, blood glucose and HOMA-IR). MHO were classified as follows by Damanhoury et al (2018). The Student´s T test or One Way ANOVA and Mann- Whitney or Kruskall Wallis test were reported according to distribution. For categorical variable the chisquare and Fisher´s exact test were used. To verify the association between WHO and HEI, logistic regression analyzes were performed using energy consumed, income, physical activity, sleep and WHR as adjustment variables. The significance level of 5% was adopted. Results: The sample consisted in 157 adolescents, with a similar profile between sex, age, metabolic profile (HDL- High density Lipoprotein, TG- triglycerides, blood pressure and glucose). The girls had the worst HOMA-IR (p=0,003), the lowest waist circumference (WC) (p=0,021), lowest waist-to-height ratio (WHR) (p=0,004), lowest caloric intake (p=0,002) and worst score in HEI (p=0,05) compared to boys. Among the adolescents 14,6% were MHO and 85,35% were MUO. Adolescents MHO had the lowest sodium consumption, had higher income (p=0,026), lowest waist circumference (p=0,001) and better HOMA-IR (p=0,017). We observe that higher HEI scores in boys were a protective factor against metabolic abnormalities (OD 95% IC 0,77 (0,6-0,99). Conclusions: MHO adolescents have less sodium intake and a better income profile. Boys have higher WC, RCE, higher Kcal consumption and better HEI score; abetter quality of food was protective factor in relation to metabolic changes in boys.